2012
DOI: 10.1071/an11208
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen metabolism and recycling in yaks (Bos grunniens) offered a forage - concentrate diet differing in N concentration

Abstract: An experiment was conducted to characterise N use efficiency and quantify urea fluxes in yaks offered four levels of dietary N (1.43%, 1.97%, 2.45% and 2.90% of diet DM) in a 4 · 4 Latin square design. The incremental increase in N intake linearly increased N retention (P = 0.003) and the excretion of urinary N (P < 0.001), but no difference (P > 0.05) in faecal N excretion was observed in growing yaks fed any of the four diets. Microbial N production had quadratic (P < 0.001) responses to dietary N, character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…Like in previous reports (Marini and Van Amburgh, 2003;Guo et al, 2012), we observed that the urea pool size became smaller as the level of dietary N decreased. In contrast, turnover time decreased with increasing dietary N, reflecting increases in GER and kidney urea clearance as dietary N increased.…”
Section: Effect Of N Intake On Urea Pool Size and Urea Clearance By Tsupporting
confidence: 69%
See 3 more Smart Citations
“…Like in previous reports (Marini and Van Amburgh, 2003;Guo et al, 2012), we observed that the urea pool size became smaller as the level of dietary N decreased. In contrast, turnover time decreased with increasing dietary N, reflecting increases in GER and kidney urea clearance as dietary N increased.…”
Section: Effect Of N Intake On Urea Pool Size and Urea Clearance By Tsupporting
confidence: 69%
“…To date, physiological adaptation to inadequate N resources and feed supply have been investigated in dairy cattle (Marini and Van Amburgh, 2003), beef cattle (Archibeque et al, 2001;Huntington et al, 2009;Titgemeyer et al, 2012), yak (Guo et al, 2012), sheep (Sarraseca et al, 1998;Lobley et al, 2000;Marini et al, 2004), and goats (Brun-Bellut, 1997). The efficiency of N utilization and the ability of the animal to adapt to low N diets is affected by various factors, such as the dietary energy content, N digestion, urea kinetics, rumen microbial activity, urea reabsorption by the kidney, the physiological state of the animal, and animal species (Wang et al, 2011;Marini et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent research declared that yak have developed special regulating mechanisms in the kidney in terms of glomerular filtration rate and purine derivative excretion to help the animal to adapt the alpine environment (Wang et al, 2009). Another paper from the same research team showed that the yak might be more efficient at utilizing N in a harsh environment than are cattle (Guo et al, 2012). However, there is no information on yak’ fat storage mobilization and metabolism during starvation.…”
Section: Introductionmentioning
confidence: 99%